Understanding the mathematics training of futures pedagogues through narratives - Julio, Rejane Siqueira; Gomes Da Silva, Guilherme Henrique [UNESP] (FapUNIFESP (SciELO), 2018)
This paper addresses the mathematics training of prospective elementary teachers. It aims to analyze written and oral narratives produced by students from a Pedagogy program of a Brazilian Federal University. We take into account that the mathematical training of these students has started before the access to higher education. Thus, we consider it is important to understand this previous knowledge in order to contribute to these students' training process. During the narratives analysis, we built the following themes: general conception about mathematics; teacher posture; the use of mathematics in everyday practices; ways to deal with mathematical contents; mathematical content mostly quoted; and emphasis on literacy. In addition, we discuss in this paper specifics mathematics contents from Pedagogy programs. The discussions converge to the role of teacher trainer when she/he is faced with the lack of time to address contents and methodologies of mathematics education and with the difficulties brought by her/him students since their basic schooling. Considering a training perspective, we emphasize the care with microaggressions related to mathematics contents and the meaning production related to mathematics teaching and learning.
Compreendendo a Formação Matemática de Futuros Pedagogos por meio de Narrativas
Keywords: Curriculum; Higher education; Mathematical training of elementary teacher; Mathematics education; Narratives